P3 11 A Mincey Situation - Brewer, Lois; Bates, Ethan; Sadler, Tommy; Smith, Kennedy (Physics Special Topics, 2022)
With Christmas coming up, it is always a joy to see and spend time with your family. Although, sometimes they can really make your blood boil as you sit there trying to scoff mince pies and count Monopoly money. Speaking of mince pies and blood boiling, here we estimate the number of mince pies an individual would need to eat to make their blood boil to be around 19.5 mince pies, assuming 100% energy efficiency.